ANALISIS KESEIMBANGAN WATER DISPENSER ASSEMBLY LINE MENGGUNAKAN METODE RANKED POSITIONAL WEIGHT, REGION APPROACH, DAN LARGEST CANDIDATE RULE DI PT. PANASONIC MANUFACTURING INDONESIA - Mutia Aprilianti (2023)
PT. Panasonic Manufacturing Indonesia is one of the largest electronic goods manufacturers in Indonesia which produces several electronic products, one of which is a water dispenser. Looking at the graphs for the last 6 months, the level of line efficiency in the assembly line is below the company's standard and there are several work stations that are bottlenecks. Therefore, an analysis is needed regarding the even distribution of the water dispenser assembly line in order to achieve company standards. To support this analysis, it is necessary to test data adequacy, data uniformity, and standard time calculations in the assembly process. Then, using the Ranked Positional Weight, Region Approach, and Largest Candidate Rule methods to analyze the balance of the track. Based on the results of data processing, the actual condition of line efficiency reached 121.41% with a balance delay of -21.41% which illustrates the number of work stations experiencing bottlenecks with an initial condition of 14 work stations. After being analyzed using the RPW, RA, and LCR methods, an increase in line efficiency of 80.9% and a balance delay of 19.1% was obtained. Meanwhile, the smoothness index for the RPW and LCR methods was 145.715 seconds and RA 145.790 seconds with the addition of 21 work stations.